Mycolicibacterium lacusdiani sp. nov., an Attached Bacterium of Microcystis aeruginosa - Xiao, Yao; Chen, Jian; Chen, Min; Deng, Shao-Ji; Xiong, Zhi-Qian; Tian, Bao-Yu; Zhang, Bing-Huo (Frontiers in Microbiology, 2022)
In eutrophic water, attached bacteria of Microcystis play an important role in the formation, development, and degradation of Microcystis blooms. A novel actinobacterium, designated JXJ CY 35T, was isolated from culture mass of Microcystis aeruginosa FACHB-905 (Maf) collected from Lake Dianchi, Yunnan Province, China. Strain JXJ CY 35T was gram-positive, aerobic, with short rod-shaped cells, positive for catalase and negative for oxidase. The isolate was able to grow at 10.0-32.0°C, pH 4.0-10.0 and tolerate up to 5.0% (w/v) NaCl, with optimal growth at 28°C, pH 7.0-8.0 and 0% (w/v) NaCl. Cell-wall peptidoglycan contains aspartic acid, glutamic acid, glycine and alanine, with mannose, ribose, galactose and arabinos as whole-cell sugars. Polar lipids consist of diphosphatidylglycerol (DPG), phosphatidylethanolamine (PE), glycolipid (GL1-2), phosphoglycolipid (PGL) and unidentified lipid (L1). The predominant menaquinone was MK-9. Major fatty acids (>10%) were C17:1ω7c (36.96%), C18:1ω9c (18.94%) and C16:1ω6c (13.38%). The complete genome sequence of strain JXJ CY 38T was 6,138,096 bp in size with a DNA G + C content of 68.3%. Based on 16S rRNA gene sequences, it shared the most similarity of 98.2% with Mycolicibacterium arabiense DSM 45768T. On the basis of the above taxonomic data and differences in physiological characteristics from the closely related type strains, strain JXJ CY 35T was determined to represent a novel species of genus Mycolicibacterium, for which the name Mycolicibacterium lacusdiani sp. nov., is proposed. The type strain is JXJ CY 35T (=KCTC 49379T=CGMCC 1.17501T). Different inoculation dosages of the type strain JXJ CY 35T could exhibit different effects on the growth of Maf and its toxin synthesis and release. Strain JXJ CY 35T could promote the growth of Maf by providing it with available phosphorus, nitrogen and probably other unknown substances.